Oral nystatin prophylaxis and neonatal fungal infections. Issue 6 (25th March 2009) - Howell, A; Isaacs, D; Halliday, R; Infections, The Australasian Study Group for Neonatal
Abstract : Background: The value of antifungal prophylaxis depends partly on the incidence of neonatal fungal infection. We compared the incidence of fungal infection in babies in neonatal units which do and do not give antifungal prophylaxis using oral nystatin. Methods: Prospective, multi-centre surveillance study from 1993 to 2006 of invasive fungal infection, defined as positive blood or cerebrospinal fluid culture, in babies <1500 g birth weight in neonatal units in Australia and New Zealand. Results: There were 118 episodes of invasive fungal infection in 14 778 babies <1500 g, an incidence of 0.80% (95% confidence interval (CI) 0.66 to 0.94%). All infections were due to Candida species, mostly C. albicans (74, 62.7%) and C. parapsilosis (39, 33.1%). The mortality was 16.5%. The incidence was 0.54% (0.38 to 0.70%) for babies <1500 g in units using selective or universal oral nystatin prophylaxis and 1.23% (0.84 to 1.62%) in units using no prophylaxis (p<0.001). The incidence of infection in babies <1000 g was 1.78% (106/5948) (95% CI 1.44 to 2.12%). The incidence was 1.23% (0.92 to 1.54%) for babies <1000 g in units using nystatin prophylaxis and 2.67% (1.97 to 3.37%) in units using no prophylaxis (p<0.001). Conclusions: The incidence of neonatal fungal infection was low in Australia and New Zealand, even without antifungal prophylaxis. Antifungal prophylaxis with oral nystatin was associated with a significantly lower incidence of fungal infection compared with no prophylaxis.